Postoperative sigmoidoscopy and biopsy after elective endovascular and open aortic surgery for preventing mortality by Colonic Ischemia (PSB-Aorta-CI): protocol for a prospective study - Gomes dos Santos Ferreira Rebelo, Artur Luis; Ronellenfitsch, Ulrich; Partsakhashvili, Jumber; John, Endres; Sekulla, Carsten; Krug, Sebastian; Rosendahl, Jonas; Michl, Patrick; Ukkat, Jörg; Kleeff, Jörg H. (JMIR Research Protocols, 2022)
aortic; colonic; ischemia; surgery; vascular; cardiology; heart disease; patient treatment; clinical decision; health safety; risk assessment